URGENSI TARJÎH DALAM ISTINBÂTH HUKUM ISLAM - Ainol Yaqin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Tarjîh  is a method tool of istinbâth in Islamic law. The method is formulated by ulama’ ushul to find a bright spot to set Islamic law among the opposite theorems. The existence of the method is very important in choosing strong/pure al-Qur’an texts and Hadits from some of the other Hadits related to the law problems. Therefore, the ulama’ ushul fiqh al-Hanafiyyah, al-Mâlikiyyah, al-Syâfi’iyyah, al-Hanâbilah dan al-Zhâhiriyyah construct steps to take to solve the dead end in ijtihad when they face some contradictory theorems. Al-Hanafiyyah takes four ways to deal with two or more contradictory al-Qur’an texts and Hadits. First, al-naskh (to clear, to cancel), second, al-tarjîh (to strengthen, to favor), third, al-jam’ wa al-tawfiq (to combine, to compromise) and the last is tasâquth al-dalilayn (to break and move to another theorems). While, methods used to deal with the contradictory theorems by al-Mâlikiyyah, al-Syâfî’iyyah, al-Hanâbilah dan al-Zhâhiriyyah is first, al-jam’ wa al-tawfiq bayn al muta’aridlayn bi wajh maqbul (collect and compromise the contradictory theorems from one side), second, al-tarjîh, the third, al-naskh and the last is tasâquth al-dalilayn. Tarjîh can be done by considering some sides, those are, a. Sanad side (The chain of Hadits reader), b. Matan side (Hadits text), c. Law contained in the law side (text or Hadits) and d. translation from other theorems.